STUDY ON THE STRATEGIES OF SEMARANG CONTAINER TERMINAL IN FACING ASEAN ECONOMIC COMMUNITY 2015 - Arina Narulitasari; Paniya Paniya; Erika Devie (JOBS (Jurnal Of Business Studies), 2015)
At the 12th ASEAN Summit, the leader of ASEAN members agree to accelerate the establishmentof ASEAN Community in 2015 and transform ASEAN region with free flow of goods; free flow ofservices; free flow of investment; free flow of skilled labor; and free flow of capital. The role ofport of port is crucial in economy development, the presence of capability port plays major rolein supporting people and goods mobility especially the presence of AEC whose element is freeflow of goods in ASEAN countries. To face AEC, people of Indonesia generally and Central Javaespecially need some strategies that they might not be a spectator in their own country.This undergraduate thesis uses qualitative method to describe the strategies of SemarangContainer Terminal in facing AEC and analyzed it by SWOT Analysis, SWOT diagram, and SWOT matrix. The result of IFAS is 3.6 and EFAS is 3.48, so that the position of Semarang Container Terminal is in quadrant 1, supporting aggressive strategy. The aggressive strategiesare maximizing the use of the existing facilities to increase company’s performance, reprogramRoad Show, and do socialization to stakeholder in cooperation with Central Java andYogyakarta government (SO Strategy in SWOT matrix).Key words: strategy, Semarang Container Terminal, ASEAN Economic Community, strength,opportunity.